2010
DOI: 10.1007/s10165-010-0308-4
|View full text |Cite
|
Sign up to set email alerts
|

A case of adalimumab-associated interstitial pneumonia with rheumatoid arthritis

Abstract: A 64-year-old woman with rheumatoid arthritis (RA) began to complain of recurrent non-productive cough 5 months after starting adalimumab. The chest radiograph and high-resolution computed tomographic findings revealed diffuse ground-glass attenuation. Her clinical course suggested that interstitial pneumonia (IP) may have been induced by adalimumab, and she was successfully treated with a medium dose of corticosteroid. This case indicates that adalimumab-associated IP should be considered if a RA patient deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
10
0
4
Order By: Relevance
“…( 6 ) Symptoms can appear from one month ( 9 ) to three and a half years after treatment initiation. ( 7 ) Findings on HRCT can include ground-glass opacities, foci of consolidation, reticulated patterns, and traction bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 6 ) Symptoms can appear from one month ( 9 ) to three and a half years after treatment initiation. ( 7 ) Findings on HRCT can include ground-glass opacities, foci of consolidation, reticulated patterns, and traction bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…( 7 ) Findings on HRCT can include ground-glass opacities, foci of consolidation, reticulated patterns, and traction bronchiectasis. ( 6 , 8 ) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports of interstitial pneumonia after TNF blocker use continue to appear 510 511. However, in an analysis from a British registry, the mortality of RA patients with ILD following treatment with TNF blockers was not higher than with traditional DMARD therapy (23% vs 21%), despite probable channelling bias toward more use of TNF blockers in those with underlying ILD or organising pneumonia (category C evidence) 512…”
Section: Updatementioning
confidence: 99%
“…However, the adverse effects of TNF-α inhibitors include opportunistic infections, liver injury, and drug-associated interstitial lung disease. Several reports have so far described TNF-α inhibitors-induced interstitial pneumonia (1)(2)(3)(4)(5). On the other hand, a few reports have suggested that TNF-α inhibitors may be an important therapeutic strategy in the management of RA-associated lung disease (6).…”
Section: Introductionmentioning
confidence: 99%